1997
DOI: 10.1074/jbc.272.51.32419
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chondromodulin I as a Novel Endothelial Cell Growth Inhibitor

Abstract: Cartilage is unique among tissues of mesenchymal origin in that it is resistant to vascular invasion due to an intrinsic angiogenic inhibitor. During endochondral bone formation, however, calcified cartilage formed in the center of the cartilaginous bone rudiment allows vascular invasion, which initiates the replacement of cartilage by bone. The transition of cartilage from the angioresistant to the angiogenic status thus plays a key role in bone formation. However, the molecular basis of this phenotypic trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
55
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(59 citation statements)
references
References 42 publications
3
55
0
1
Order By: Relevance
“…The mRNA for ChM-I was shown to be abundant in fetal cartilage and, although present in adult cartilage, was reduced to 5% of the fetal level (8). Immunohistochemistry and in situ hybridization localized ChM-I and its mRNA to the interterritorial matrix of the avascular zones of growth plate cartilage (3). ChM-I stimulates DNA synthesis and proteoglycan biosynthesis in the presence of basic fibroblast growth factor 2 (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mRNA for ChM-I was shown to be abundant in fetal cartilage and, although present in adult cartilage, was reduced to 5% of the fetal level (8). Immunohistochemistry and in situ hybridization localized ChM-I and its mRNA to the interterritorial matrix of the avascular zones of growth plate cartilage (3). ChM-I stimulates DNA synthesis and proteoglycan biosynthesis in the presence of basic fibroblast growth factor 2 (2).…”
mentioning
confidence: 99%
“…The pattern of ChM-I expression and the fact that purified ChM-I inhibited DNA synthesis and proliferation in vascular endothelial cells as well as tube morphogenesis in vitro (3) suggest that one role for ChM-I is as an inhibitor of angiogenesis. However, the abundance of ChM-I in fetal cartilage suggests that it may have other roles in chondrocyte growth modulation.…”
mentioning
confidence: 99%
“…No expression of the ChM-I gene is observed in bone tissues developing after vascular invasion in the area adjacent to hypertrophic chondrocytes (3). In matured limbs, the expression of the ChM-I gene is limited to cells in the resting, proliferating, and early hypertrophic zone of the growth plate (2)(3)(4). These results suggest that the expression of the ChM-I gene is regulated strictly in a cell-and stage-related manner, although the molecular mechanisms leading to this spatiotemporal expression have not been elucidated.…”
mentioning
confidence: 72%
“…Chondromodulin-I (ChM-I) 1 is a 25-kDa glycoprotein originally purified from bovine epiphyseal cartilage on the basis of growth-promoting activity for chondrocytes (1) and subsequently revealed to be a potent vascular endothelial cell growth inhibitor (2). During embryonal development, the expression of the ChM-I gene is first observed in all of the cartilaginous tissues, which are composed of prehypertrophic chondrocytes (3).…”
mentioning
confidence: 99%
“…The major biological functions of ChM-I are to stimulate the proliferation of chondrocytes and inhibit angiogenesis [8][9][10]. Several reports have indicated that, in human salivary pleomorphic adenomas, ChM-I might be expressed in the lacunar cells of the chondroid matrix and in the myoepithelial cells [13,14].…”
mentioning
confidence: 99%